Urological anomalies in OHVIRA syndrome (Herlyn-Werner-Wunderlich syndrome) - K. Lodeikina; I. M. Kagantsov; S. A. Karavaeva; N. A. Kokhreidze (Вестник урологии, 2022)
We provide a systematic review of articles related to OHVIRA syndrome (Herlyn-Werner-Wunderlich syndrome), found in PubMed/MedLine, Web of Science, Scopus, Scirus, The Cochrane Library and eLIBRARy to show how the urological component of this congenital malformation, previously considered as a concomitant anomaly, has become an important diagnostic marker. Several attempts were made to classify this condition, and they got more complex to include these variants of abnormalities of the kidney and ureter that were found due to advances in imaging technology. As a result, the understanding of the medical community about the OHVIRA syndrome has gradually changed over the past hundred years, and the growing interest of pediatric urologists and surgeons, in turn, has contributed to the early diagnosis of the syndrome and the improvement of examination methods.